2020
DOI: 10.1016/j.corsci.2019.108365
|View full text |Cite
|
Sign up to set email alerts
|

The role of niobium carbides in the localised corrosion initiation of 20Cr-25Ni-Nb advanced gas-cooled reactor fuel cladding

Abstract: The role of niobium carbides in the localised corrosion initiation of 20Cr-25Ni-Nb advanced gas-cooled reactor fuel cladding. Corrosion Science, [108365].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
5
24
0
Order By: Relevance
“…Such an acidic electrolyte led to the preferential dissolution of both the grain boundaries and the matrix surrounding the NbCs. Therefore, these observations could suggest that NbCs might act as preferential pit initiation sites, as demonstrated by Clark and its co-workers [43]. However, considering the very small size of the NbCs, it was not trivial to establish a clear relationship between pit initiation and NbCs.…”
Section: Study Of the Stable Pitsmentioning
confidence: 72%
See 1 more Smart Citation
“…Such an acidic electrolyte led to the preferential dissolution of both the grain boundaries and the matrix surrounding the NbCs. Therefore, these observations could suggest that NbCs might act as preferential pit initiation sites, as demonstrated by Clark and its co-workers [43]. However, considering the very small size of the NbCs, it was not trivial to establish a clear relationship between pit initiation and NbCs.…”
Section: Study Of the Stable Pitsmentioning
confidence: 72%
“…To better evaluate the susceptibility to pitting corrosion of the 17-4 PH MSS depending on the forming process, stable pits were first characterised: a current density of 1 mA cm − ² was applied on 1-cm² samples in order to compare both the density and morphology of the stable pits, for a similar charge passed for the different microstructures. Indeed, recent work of Clark and its co-workers demonstrated the nobility of NbC precipitates in austenitic stainless steels [43]. The authors suggested that NbC precipitates were cathodic with respect to the matrix and could create a micro galvanic couple promoting the initiation of localised corrosion.…”
Section: Study Of the Stable Pitsmentioning
confidence: 99%
“…The NaOH pH-moderation of these ponds is used to inhibit corrosion of the stainless steel cladding. The 20Cr-25Ni-Nb alloy is stabilised by ~0.6% niobium (Nb) which precipitates as niobium carbide (NbC) during the manufacturing process [5]. Despite Nb stabilisation, during reactor operation a small proportion of fuel cladding can become sensitised through an alternative mechanism, known as radiation induced segregation (RIS), which leads to a redistribution of alloying elements at the microstructural level (notably, Cr diffusion away from grain boundaries), rendering the alloy sensitised [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…The 20Cr-25Ni-Nb alloy is stabilised by ~0.6% niobium (Nb) which precipitates as niobium carbide (NbC) during the manufacturing process [5]. Despite Nb stabilisation, during reactor operation a small proportion of fuel cladding can become sensitised through an alternative mechanism, known as radiation induced segregation (RIS), which leads to a redistribution of alloying elements at the microstructural level (notably, Cr diffusion away from grain boundaries), rendering the alloy sensitised [5] [6] [7]. The alloy can also be sensitised through the use of a two-stage heat treatment which causes Cr depletion at grain boundaries by the formation of Cr carbide precipitates [5] [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation